Las prestaciones sociales y beneficios legales en pymes del sector de servicios lúdicos y su relación con la vinculación laboral (2019)
The pymes in Colombia specifically in the city of Bogotá lack knowledge and do not pay the necessary importance to the rights and obligations they have with workers, at the same time workers present this ignorance, does not enforce what is stipulated and everything that the Colombia law supports the worker. In the same way to obtain a better working climate, reduce costs and other benefits that can be obtained from a correct linkage, it must be evaluated and make a decision about the type of assertive linkage according to the activities to be carried out, complying with all the mandatory benefits and benefits can since the consequences of non-compliance with these benefits and benefits can lead to fines, sanctions, demands guaranteed by the substantive work code.